Challenging the Need for Deep Seabed Mining From the Perspective of Metal Demand, Biodiversity, Ecosystems Services, and Benefit Sharing - Miller, K. A.; Brigden, K.; Santillo, D.; Currie, D.; Johnston, P.; Thompson, K. F. (Frontiers in Marine Science, 2021)
The extraction of minerals from the seabed of the deep oceans is of increasing interest to investors, mining companies and some coastal states. To date, no commercial-scale deep seabed mining has taken place but there is considerable pressure for minerals mining to become an economic reality, including to supply the projected demand for metals to support a global transition to renewable energy. At the same time, the full environmental impacts of deep seabed mining are difficult to predict but are expected to be highly damaging, both within, and perhaps well beyond, the areas mined. Here, we reflect on the considerable uncertainties that exist in relation to deep seabed mining. In particular, we provide a perspective on: (1) arguments that deep seabed mining is needed to supply minerals for the green energy revolution, using the electric vehicle battery industry as an illustration; (2) risks to biodiversity, ecosystem function and related ecosystem services; and (3) the lack of equitable benefit sharing to the global community now and for future generations. We explore the justification for a global moratorium on deep seabed mining to ensure protection of marine ecosystems, the need to focus on baseline research, and how improved governance of targeted marine regions could be key to the preservation and conservation of the ocean biome.